Construction Manual for Polymers + Membranes: Materials, Semi-finished Products, Form Finding, Design - Knippers, Jan (DETAIL Construction Manuals, 2011)
Whether it be as translucent sheets, broadly stretched membranes, and inflated foil cushions or in graceful, organic curves, architecture today is utilizing plastics in the most disparate forms and for a wide variety of purposes. Innovative technical developments are constantly improving its material properties; at the same time, there is a growing new awareness of its potential as a construction material. While plastics used to be employed primarily as an inexpensive variant on traditional building materials, they are increasingly regarded in the construction world today as a serious and viable alternative, be it as supporting structures, roofs, facades, or elements of interior design and decoration. Thanks in large part to this inherent self-sufficiency, plastics are currently enjoying an unprecedented surge in popularity, even among the international architectural avant-garde - as multiwall sheets or corrugated, fiber-reinforced panels, or as filling between glass panes. And the new generation of ecological bioplastics also pays tribute to the debate on sustainability, ridding plastics of their lingering reputation as environmental offenders. From the history of plastics and membranes in architecture to their material properties and requirements in construction and design, the Plastics and Membranes Construction Manual cuts to the chase, providing the kind of solid and comprehensive overview of the subject that readers have come to expect from the Im DETAIL series. Selected project examples round off the reference work and make it indispensable for the day-to-day life of the professional planner and for every architecture library.